Automated Hydroponics Notification System Using IOT - Boonneua, Wrintorn; Chai-Arayalert, Supaporn; Boonnam, Nathaphon (International Journal of Interactive Mobile Technologies (iJIM), 2022)
This research was conducted to increase the productivity of farmers and to plan the planting of crops by farmers when using a hydroponics system that controls various environmental conditions, in which plant growth factors such as temperature, humidity, water temperature, pH and electrical conductivity are important factors for hydroponics. The Internet of Things control and notifications enabling farmers to quickly modify and improve their crop treatment. This research focuses on use of the Internet of Things to control plant growth factors. Displays and alerts are communicated to the user through a web application where, when comparing plants with controlled growth factors and unregulated systems, it can be seen controlled plant growth factors are in the desired range of the plant, whereas in uncontrolled systems there are unwanted values range of plant, which can cause the plant to not fully grow or even to wither. In this system, farmers are able to view plant growth factor data and can retrospectively view graphs displayed on the web application by this controlled system when the measuring sensors in the system are in range that plants do not want. It prompts farmers to manage the system, which allows them to fix the system quickly and with minimal damage to crops.